Arbuscular mycorrhizal fungi enhance nitrogen assimilation and drought adaptability in tea plants by promoting amino acid accumulation - Wu, Xiao-Long; Hao, Yong; Lu, Wei; Liu, Chun-Yan; He, Jia-Dong (Frontiers in Plant Science, 2024)
The development and quality of tea plants (Camellia sinensis (L.) O. Ktze.) are greatly hampered by drought stress (DS), which affects them in a number of ways, including by interfering with their metabolism of nitrogen (N). Arbuscular mycorrhizal fungi (AMF) are known to enhance water and nutrient absorption in plants, but their specific effects on tea plant N metabolism under DS and the associated regulatory mechanisms remain unclear. This study aimed to evaluate the impact of Claroideoglomus etunicatum inoculation on N assimilation in tea plants (C. sinensis cv. Fuding Dabaicha) under well-watered (WW) and DS conditions, and to explore potential molecular mechanisms. After 8 weeks of DS treatment, root mycorrhizal colonization was significantly inhibited, and the biomass of tea shoots and roots, as well as the contents of various amino acids (AAs) were reduced. However, AMF inoculation significantly increased the contents of tea polyphenols and catechins in leaves by 13.74%-36.90% under both WW and DS conditions. Additionally, mycorrhizal colonization notably increased N content by 12.65%-35.70%, various AAs by 11.88%-325.42%, and enzymatic activities associated with N metabolism by 3.80%-147.62% in both leaves and roots. Gene expression analysis revealed a universal upregulation of N assimilation-related genes (CsAMT1;2, CsAMT3;1, CsGS1, CsNADH-GOGAT, CsTS2, CsGGT1, and CsADC) in AMF-colonized tea roots, regardless of water status. Under DS condition, AMF inoculation significantly upregulated the expressions of CsNRT1;2, CsNRT1;5, CsNRT2;5, CsNR, CsGS1, CsGDH1, CsGDH2, CsTS2, CsGGT1, CsGGT3, and CsSAMDC in tea leaves. These findings suggest that AMF improved tea plant adaptability to DS by enhancing N absorption and assimilation, accompanied by the synthesis and accumulation of various AAs, such as Glu, Gln, Asp, Lys, Arg, GABA and Pro. This is achieved through the upregulation of N metabolism-related genes and the activation of related enzymes in tea plants under DS condition. These findings provide valuable insights into the role of AMF in regulating tea plant N metabolism and enhancing stress tolerance.